Antibacterial Mechanism of Bacteriocin of Lactococcus lactis Q13 against Methicillin-Resistant Staphylococcus aureus - LIU Shuang, WANG Jinli, LIANG Anjian, YANG Yangyang, ZHU Chenglin, TANG Junni (Shipin Kexue, 2025)
The antibacterial mechanism of bacteriocin produced by Lactococcus lactis Q13 against methicillin-resistant Staphylococcus aureus (MRSA) was investigated in this study. The minimum inhibitory concentration (MIC) of the bacteriocin was tested, and its effects on bacterial growth, biofilm formation and DNA replication were evaluated. Meanwhile, quantitative polymerase chain reaction (qPCR) was used to study the effect of the bacteriocin on the expression of biofilm formation-related genes, virulence genes and genes related to DNA replication in MRSA. The results showed that bacteriocin Q13 could inhibit the growth of MRSA, with an MIC of 0.78 mg/mL. Scanning electron microscopy showed that bacteriocin Q13 could destroy the cell membrane of MRSA, leading to the leakage of intracellular contents. The leakage of nucleic acid and protein from MRSA cells increased obviously at all concentrations of bacteriocin Q13. At 1 MIC concentration, the leakage of nucleic acid and protein increased by 614.71% and 1 173.91%, respectively. The bacteriocin could inhibit and eradicate the biofilm of MRSA. At 1 MIC concentration, the inhibition rate and eradication rate of MRSA biofilm were 95.03% and 56.14%, respectively. Both synergistic and antagonistic effects were observed between antibiotics and bacteriocin Q13. The DNA content of MRSA cells decreased after treatment with the bacteriocin, and the expression of drug resistance genes, membrane formation-related genes, virulence genes and DNA replication-related genes was down-regulated. This study showed the potential of bacteriocin Q13 as a natural preservative in the food industry.